Typology of sociotechnical transition pathways - Geels, Frank W.; Schot, Johan (Research Policy)
Contributing to debates about transitions and system changes, this art icle has two aims. First, it uses criticisms on the multi-level perspe ctive as stepping stones for further conceptual refinements. Second, i t develops a typology of four transition pathways: transformation, rec onfiguration, technological substitution, and de-alignment and re-alig nment. These pathways differ in combinations of timing and nature of m ulti-level interactions. They are illustrated with historical examples .